Answer:
The choices were typed wrong, but we can find the inverse of each option.
For function
the inverse is the same function
, because an inverse of a function is where their composition gives the independent variable as unique result.
If we do that with each function, we have:
; where
and
, we have
![f((g(x))=x\\x=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nd9y59o659k41g40b8xtpml2i3j7yl5ind.png)
So they are inverse.
For
its inverse would be
, because
![f(g(x))=2((1)/(2)x)=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bp8ztj3vqfyodqdxp0kbx672cp745s9st9.png)
For
, its inverse is
, because
![f(g(x))=4((1)/(4)x)=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/siv9aova9obwj3ffow23jv4jz27kfb9plf.png)
For
, its inverse is
, because
![f(g(x))=-8(-(1)/(8)x)=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p44lqt9mg9039tmh7674n0h858htgoplrf.png)
There you have all inverses. Basically, if their composition results in
, that means they are inverse.